An Update on Italian Stroke Organization Guidelines on Carotid Endarterectomy and Stenting. (October 2014) - Lanza, Gaetano; Ricci, Stefano; Setacci, Carlo; Castelli, Patrizio; Novalil, Claudio; Pratesi, Carlo; Speziale, Francesco; Cremonesi, Alberto; Morlacchi, Ernesto; Lanza, Jessica; Santalucia, Paola; Zaninelli, Augusto; et al.
One hundred and fifty-three authors, 45 Italian scientific societies, and two Italian patients' associations participated in drafting the Italian Stroke Organization document, which has become the national guideline for the prevention and treatment of stroke in Italy. For the surgical therapy section of the Italian Stroke Organization document, the main trials on carotid endoarterectomy and stenting were critically reviewed in order to formulate recommendations for these procedures. Recommendations are presented here for the referral of patients to either carotid endarterectomy or stenting on the basis of whether carotid stenosis is symptomatic or asymptomatic.